Uji Efektivitas Gulma Lantana Camara Sebagai Pestisida Nabati Hama Necrobia rufipes on Kopra - Betty K Lahati; Zauzah Abdulatif; Rahmatia Baco; Hayun Abdullah (Universitas Khairun, 2022)
Necrobia is the main pest in attacking copra in storage. Copra farmers in North Maluku are often worried about this pest because it causes considerable losses, especially for export materials and for the welfare of the farmers. Therefore, this study uses Lantana camara, a vegetable pesticide known as a weed that grows wild as an alternative to synthetic pesticides that cause pest resistance. The purpose of this study was to test the effectiveness of Lantana camara weed as a vegetable pesticide to control Necrobia sp. The research method used a completely randomized design (CRD) with 4 treatments namely control (Lc0) , Lantana camara (Lc1) 5 grams, Lantana camara (Lc2) 10 grams and Lantana camara (Lc3) 15 grams repeated 4 times, with 20 test samples. (second instar larvae of Necrobia sp) for each treatment. With the parameters of the Mortality test of Necrobia pests, Copra Shrinkage and as a support by observing the condition of the warehouse. The results showed that the higher the dose of Lc, the greater the mortality of Necrobia sp. Also at a dose of 15 grams it can produce smaller copra losses with 12.36% copra losses. The condition of the warehouse in Bastiong, Central Ternate Village, still does not have good facilities for copra storage such as floor mats, ventilation and there is only one main door.Â Keywords:Â Necrobia rufipes, Lantana camara, Copra